Influence of Oil Content on Solution Load Ethanol-Soda Delignification of Oil Palm Mesocarp Fiber - Taharuddin, Taharuddin; Iryani, Dewi Agustina; Eka Wahyu, Megananda (Jurnal Rekayasa Kimia & Lingkungan, 2018)
Mesocarp fiber palm oil industrial waste can be processed into pulp, but this fiber still contains oil with varying levels. The difference oil content in fiber affects the amount of cooking solution required to make mesocarp waste into pulp. This study consists of two stages, namely the pretreatment stage of oil extraction to obtain variations in oil content in the mesocarp fiber waste and the delignification stage using the NaOH-ethanol solution with the ratio of solids:solvent is varied to 1: 8, 1:10 and 1:12. Oil content of the fiber was analyzed, it is consist of 9,5% oil. To vary the oil content, the fibers are soaked in ethanol at room temperature and the levels drop to 7%. And soaking at 40C can lower the oil content drop to 2%. The obtained pulp had the largest cellulose content 50.77% from delignified product from fiber with 7.6% oil content and solids:solvent ratio: 1:10. While the lowest lignin that was 7.39% obtained at 2.5% oil content. In the delignification process with ratio 1:12, pulp produced is decreased in cellulose content and from FTIR results it is known that it occurs because of the degraded cellulose during the delignification process.